Academic staff as 'transition managers' in interdisciplinary, international MA education: A Danish case study. Issue 2 (1st June 2019) - Tange, Hanne
Abstract : The article builds on an empirical study of knowledge practices in international, interdisciplinary MA education, foregrounding the role of academic staff in identifying and explicating academic norms to students recruited from different subject areas and institutions. A central theme is transition, which refers to the state of liminality that postgraduates can experience when new to a discipline, institution and sociocultural context. I argue for lecturers as 'transition managers' who may ease students' transfer into an unfamiliar academic culture. This argument is explored in an analysis of interview data collected from four MA courses, which suggests that lecturers' transition management involves an awareness of classroom diversity, an acceptance of responsibility for academic socialisation and the development of new pedagogic practices.